Long-term monitoring of natural hydrogen superficial emissions in a brazilian cratonic environment. Sporadic large pulses versus daily periodic emissions. (19th January 2021) - Moretti, Isabelle; Prinzhofer, Alain; Françolin, João; Pacheco, Cleuton; Rosanne, Maria; Rupin, Fabian; Mertens, Jan
Abstract: In many basins, hydrogen-emitting structures are now observed, but the estimation of the H2 flow leading to their formation remains poorly constrained since all data show that the H2 emissions are variable in space and time. We present here the data of a long-term monitoring campaign with a high density of permanent hydrogen detectors installed in 2 structures in the Minas Gerais State (Brazil). Results show that two kinds of signals are recorded, large sporadic pulses that affect the H2 content of the soil for one or two days and smaller ones, with a daily periodicity, that last 6 h and during which the near surface soil concentration usually does not exceed 200 ppm. This last signal is very regular in frequency, less in amount, and the daily maximum happens around noon or in the early afternoon. We interpret the large pulses as evidences of a deep hydrogen flux, leaking either from a reservoir located in the subsurface, from an aquifer which is degassing or, although it seems unlikely, directly from the H2 generation area. The time correlation between the pulse and the increase of the daily signal suggests that this last one corresponds to the slow release of the gas that has been captured by the soil during its transport towards the surface. This daily signal is most likely influenced by external factors such as atmospheric pressure and sub-surface bacterial activity. In map view, the lack of correlation between the highest hydrogen concentrations over time suggests that the soil is very heterogeneous and that preferential pathways exist. The results confirm that long-term monitoring, over a few months, is mandatory to catch a certain number of high pulses and so to have a better estimation of the real flow. Data also suggests that sensors with a large concentration range should be used (from 10 to several 10 4 ppm). Even if quantification of leakage doesn't help to quantify the subsurface reserves, these new data allow a more precise evaluation of the quantity of H2 released in surface by these structures, few hundred of kilo per day, and confirm the high H2 prospectivity of this basin. Highlights: Large quantities of H2 are leaking from the Sao Francisco basin. Few hundred kg of H2 per day/km 2 escape from the emitting structures. High Pulses are emitted sporadically and part of the H2 remains trapped in the soil. Remaining H2 is then slowly released following daily changes in temperature and pressure.